Embedded System Design Student’s Learning Readiness Instruments: Systematic Literature Review - Elfadil, Nazar; Ibrahim, Intisar (Frontiers in Education, 2022)
A systematic literature review that covering publications from 1992 to 2020, was carried out to determine and measuring the effects of students readiness prior to study an Embedded System design course. Furthermore, measuring such effects might shrink the gap between academically taught skills and the skills sought and requested by the industry. The review will be conducted with the objective to collect and investigate all credible and effective researches that have studied students’ learning readiness problems and solutions on embedded system design courses. Nevertheless, paper aims to extract and discuss the prominent features and techniques in the selected research articles to provide researchers and practitioners with a concise collection of suggestions and provided solutions. The findings revealed that there is yet to be an instrument specifically designed for measuring students’ readiness to learn embedded system design course. Additionally, most of the proposed instruments lacked construct clarity.